Exploring the infection process of Haliotis discus hannai to Vibrio harveyi based on changes in intestinal microbiota - Li, Yanan; Chen, Jiayao; Pan, Xinnan; Wang, Ruoyu; Zhu, Ying (Frontiers in Marine Science, 2025)
Vibrio harveyi is capable of inducing vibriosis in Haliotis discus hannai and causes enormous economic losses to marine mollusks. The intestinal microbiota plays critical roles in immune homeostasis and provides essential health benefits or poses risks to the host. However, there is still little information about the intestinal microbiota responses of H. discus hannai to V. harveyi infection. We investigated the variations in the mortality rate, pathological changes, and intestinal microbiota communities of abalone after exposure to V. harveyi. The present study investigated the intestinal microbial response to acute infection of H. discus hannai with V. harveyi at 12 hours post-infection (hpi), 32 hpi and 60 hpi by 16S rRNA gene sequencing. The results indicated that prolongation of infection exerts a significant impact on the intestinal microbial community, and within-group variability gradually decreased. At 32 hpi and 60 hpi, the relative abundance of Mycoplasmataceae and Ruminococcaceae was significantly decreased, while Vibrionaceae and Fusobacteriaceae exhibited a significant increase in relative abundance. The results demonstrated that infection of abalone with V. harveyi promoted the proliferation of pathogenic bacteria in the intestinal microbiota and thereby facilitated the development of disease in the abalones. This study aimed to explore the role of the intestinal microbiota in the pathogenic mechanism of V. harveyi infection, and provide new scientific insights into disease courses of abalones.